PENGARUH DOSIS PUPUK ORGANIK CAIR (POC) ECENG GONDOK DAN MACAM MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNCIS TEGAK (Phaseolus vulgaris L.) - Defani Ihsa Izzaty; Sugiyarto Sugiyarto; Wike Oktasari (JURNAL VIGOR, 2022)
This research aimed to determine the effect of water hyacinth Liquid Organic Fertilizer (LOF) dose and type of planting medium on the growth and yield of green beans. The research was conducted in North Magelang City (380 masl) from November 2021 to March 2022 using a factorial experiment randomized complete block design. The first factor was dose of water hyacinth LOF included 0 ml/l, 10 ml/l, 20 ml/l, and 30 ml/l. The second factor was types of planting medium include soil + rice husk charcoal (M1), soil + rice husk charcoal + goat manure (M2), and soil + rice husk charcoal + cow dung bokashi (M3). The datas were analyzed using Analysis of variace and continued with Duncan’s Multiple Range Test. The results showed that the water hyacinth LOF at a dose of 10 ml/l had a very significant effect on plant height and a dose of 20 ml/l had a significant effect on the number of pods per green bean plant. The types of planting medium were soil + rice husk charcoal (112,5 g/polybag) + goat manure (150 g/polybag) gave the best results for all observed parameters.